Efficacy of microencapsulated nucleopolyhedroviruses from Colombia as biological insecticides against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Gloria Patricia Barrera Cubillos; Juliana Andrea Gómez-Valderrama; Laura Fernanda Villamizar Rivero (Acta Agronómica)
Wettable powder formulations by microencapsulation of viral occlusion bodies (OBs) of both Spodoptera frugiperda multiple nucleopolyhedrovirus from Colombia (SfCOL) and a genotypic variant (SfCOL-A) were evaluated for controlling the fall armyworm S. frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in maize crops. Microencapsulation preserved OBs activity after three months of storage at 35ºC, where insecticidal activity loss was not greater than 12%. Additionally, the formulation protected the OBs against inactivation caused by UV-B radiation, retaining its insecticidal activity after 6 hours of UV laboratory exposure, in contrast to unformulated viral suspensions, which presented an Original Activity Remaining (OAR) between 12.1 and 50%. Under greenhouse conditions, the insect mortality was greater than 80% with microencapsulated viruses. In field trials, treatments reduced the percentage of damaged plants to levels below the economic injury level (35%) when the formulated and unformulated virus were applied at 8x1011 OBs/ha (800g/ha) dose, while the damage in the control treatment was close to 60%. Microencapsulation of SfCOL and SfCOL-A OBs provides useful advantages related to half-life and photostability of both viruses, which showed the same efficacy under field conditions.